Cerita Fantasi Siswa Kelas VII SMP Negeri 3 Singaraja - Sepri Sri Bina Br Naibaho; I Wayan Artika; I Nengah Martha (STKIP AGAMA HINDU SINGARAJA, 2023)
This study aims to describe the fantasy stories produced by students' work from various aspects, namely (1) the types of stories, (2) the power of fantasy, (3) the social scope contained in student fantasy stories. This study uses a qualitative descriptive design with the subject of fantasy stories by class VII students of SMP Negeri 3 Singaraja and the objects are types, fantasy power, and social scope of fantasy stories. data collection in this study using the documentation method. and analyzed by qualitative descriptive data analysis. The data that has been collected is processed inductively through data reduction, data presentation, and drawing conclusions. The results of this study were (1) the twenty-four works studied found that fourteen students' works raised the type of sliced ​​fantasy stories and ten total fantasy stories. Based on the types of fantasy stories, students are more likely to write sliced ​​fantasy story texts compared to fantasy story texts total, (2) students' fantasy power in fantasy stories related to characteristics, shapeshifting, supernatural beings, supernatural beings, characters and imagination in fantasy stories, (3) the social scope of fantasy stories revealed is in two social interaction fantasy stories, two social group fantasy stories, one social conflict fantasy story and one social norms and values ​​fantasy story